Mucociliary apparatus of the fallopian tubes and related pathogenetic aspects contributing to infertility and prospects for correction (analytical review) - V. I. Kobylyansky (IRBIS LLC, 2021)
Introduction. The mucociliary apparatus (MCA) of the fallopian tubes (MTр) represents one of the key mechanisms and arms in functioning of female reproductive system. A prominent role of impaired MCA in the pathogenesis of reproductive system diseases and infertility, on the one hand, as well as insufficient knowledge and elucidation of this topic, on the other hand, spurred current study.Aim: to improve our understanding about a role for reproductive system MCA and its impairment in developing diseases and infertility, as well as to identify potential perspectives for their correction.Materials and Methods. We searched for publications and analyzed literature data from 1980 to 2020 using various scientific databases, including Index Medicus, PubMed/MEDLINE, Embase, Cochrane Library and Russian scholarly journals related to gynecology, obstetrics and reproduction.Results. The analysis conducted allowed to originally assess the morpho-functional, structural-genetic features and other important aspects of MCA MTр. In addition, we demonstrated an impact of various factors on developing diverse types of pathological processes, including those capable of causing infertility. Moreover, we also elucidated a state of MCA MTр coupled to various diseases, including genetically determined disorders.Conclusion. The role of impaired MCA MTр in developing pathological process and infertility was of tremendous importance and deserves close attention, because they are often remained undiagnosed by standard methods and require use of morphological and functional research methods for verification. Perspectives for diagnostics and correction of MCA MTр disorders are further discussed.